The Art of Screening: Reasonable Efforts and Measures at the Nexus of Aid Work and Counterterrorism - Paragi, Beáta (Surveillance & Society, 2024)
Surveillance in the context of aid work refers to control over procedures, supplies, goods, and people that is deemed necessary for providing care. It is widely considered an inalienable, albeit criticized, part of care provision. International non-governmental organizations implementing aid projects in the Global South (hereafter INGOs or aid organizations), however, also screen individuals based on either conditional clauses in funding agreements in the context of counterterrorism or on their pursuing other organizational interests. While this opaque practice has raised increasing concerns both in humanitarian and development circles, it is much less known how screening is implemented and if it can be construed as (harmful) surveillance. Therefore, qualitative methods were used to explore a screening tool, the description of which is the core empirical part of this study, and to map INGO experiences and dilemmas with screening. As findings indicate, vendors delivering surveillance technology can help INGOs to navigate the complexity of sanctions and enforcement lists, ensure legal compliance, and demonstrate accountability towards donors, while the transparency obligation prescribed in data protection laws poses huge challenges. Furthermore, the right to be recognized, supported, assisted, and employed—either in the humanitarian or the development context—depends on how INGOs categorize individuals before screening and how they make decisions based on the results. The article contributes to earlier research by including screening in the conceptualization of (counter)surveillance in aid work.